Ny publikation: Exploring the Dual Nature of Engineering Education - Edström, Kristina (Högre utbildning, 2018)
Kristina Edström (2017). Exploring the dual nature of engineering education: Opportunities and challenges in integrating the academic and professional aspects in the curriculum. Doktorsavhandling i Teknik och lärande, KTH. http://kth.diva-portal.org/smash/record. jsf?pid=diva2%3A1155372&dswid=3710